Use of Tractor Mounted Ripper Tillage for Enhancing Soil Water Infiltration and Moisture Conservation in Semi-Arid Areas of Central Tanzania - Tanzania Agricultural Research Institute (International Food Policy Research Institute, 2023)
This dataset presents the data used in the study undertaken in the semi-arid area of Kiteto District in the Babati Region to address the challenge of soil plow layer compaction mainly associated with continued use of tractor mounted plow discs and cattle trampling. Trials were arranged in a mother-baby set up during the 2018/2019 cropping season whereby baby trials allow wide exposure that enables appropriate socio-economic study conditions. The mother factorial experiment was arranged in a split-plot design with two tillage treatments: Conventional farmer practice i.e. conventional tillage which involves tractor-mounted plow (CT) and rip tillage (RT) and two improved maize varieties (commercial maize variety & DT maize Variety) thus giving a total of four treatment combinations.